Nanoencapsulation of Simpur (Dillenia indica L.) Leaf Extract For Antibacterial - Robby Gus Mahardika; Shania Sakhila; Nurhadini Nurhadini (ALKIMIA, 2022)
Simpur leaf (Dillenia indica L.) as a traditional medicinal plant spread in the Bangka Belitung Islands. Secondary metabolites contained in simpur leaf extract are alkaloids, flavonoids, phenols, tannins, saponins, steroids, and terpenoids. Compounds that provide pharmacological properties such as polyphenols are unstable to the influence of temperature and high light intensity so that they are easily oxidized. The challenge to protect the damage of these compounds can be done by means of nanoencapsulation. This study aims to determine the size and efficiency of the nanoencapsulation of simpur leaf extract and its antibacterial bioactivity against Staphylococcus aureus and Escherichia coli bacteria. Manufacture of nanoencapsulation using the nanoprecipitation method with the constituent components of PCL (1.5 g), Tween 80 (50 mL), simpur leaf extract (0.15 g; 0.25 g; 0.35 g). Antibacterial activity testing using disc diffusion method. Nanoencapsulated extract mass 0.15 g; 0.25 g; and 0.35 g have sizes of 167.2 nm, respectively; 208.7 nm; and 229.1 nm and encapsulation efficiency of 88.21%; 56.77%; and 5.34%. The antibacterial activity of the nanoencapsulation and extract was more effective in inhibiting the growth of Staphylococcus aureus bacteria than Escherichia coli bacteria. Strength of activity against Staphylococcus aureus bacteria in nanoencapsulated extracts was categorized as moderate to strong and Escherichia coli bacteria in extracts were categorized as moderate.